COACHING CLINIC PENULISAN KARYA ILMIAH UNTUK MENINGKATKAN KETERAMPILAN PROFESIONAL CALON GURU DAN GURU SEKOLAH DASAR - Dina Mardiana; Fauzi, Iwan; Simpun; Thomas, Orbit; Fransiska, Carolina; Prawati, Melinda (Jurnal Pengabdian Kampus, 2024)
The Lecturer Program for Assisting Excellent Human Resources (PDPSU) is one of the schemes in the community service activity (PKM)  at the university which was carried out by the FKIP Lecturer Team from the University of Palangka Raya (UPR). This PKM-PDPSU activity was conducted for ten elementary school teachers and five prospective elementary school teachers in Palangkaraya City through coaching clinic activities in the form of training and mentoring in workshops and intensive counseling services in virtual zoom cloud meetings. The aim of this PKM-PDPSU activity is to support the superior human resources of the prospective elementary school teachers in terms of skills in writing scientific papers in the form of PTK and compiling scientific publication articles. The coaching clinic method uses an integrated direct instruction-communication approach, which will be implemented from October 2023 to February 2024. The science and technology provided by the implementation of this PKM-PDPSU activity can improve the professional knowledge and skills of elementary school teachers and prospective teachers in the field of writing scientific papers in the form of PTK. This improvement is achieved through the ability to conduct classroom action research activities and prepare reports, as well as write scientific articles and publish them in scientific journals. This is also proven by the evaluation results of the activities and performance of the participants of the coaching clinic, namely an average of 85.3 with a completion percentage of 100%. This is the conclusion that the PKM-PDPSU activities conducted by the faculty team of FKIP Palangka Raya University in 2023/2024 have been well conducted.